2003
DOI: 10.1016/j.neuroscience.2003.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between brain-derived neurotrophic factor and signal transduction modulators in the regulation of the effects of exercise on synaptic-plasticity

Abstract: Abstract-This study was designed to identify molecular mechanisms by which exercise affects synaptic-plasticity in the hippocampus, a brain area whose function, learning and memory, depends on this capability. We have focused on the central role that brain-derived neurotrophic factor (BDNF) may play in mediating the effects of exercise on synapticplasticity. In fact, this impact of exercise is exemplified by our finding that BDNF regulates the mRNA levels of two end products important for neural function, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
307
0
16

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(333 citation statements)
references
References 70 publications
10
307
0
16
Order By: Relevance
“…The time length for exercise was based on previous studies indicating increases in BDNF and synapsin I after 7 days of voluntary exercise (Vaynman et al, 2003;Griesbach et al, 2004bGriesbach et al, , 2007. Rats had ad libitum access to food and water and were maintained on a 12-h light/dark cycle.…”
Section: Voluntary Wheel Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…The time length for exercise was based on previous studies indicating increases in BDNF and synapsin I after 7 days of voluntary exercise (Vaynman et al, 2003;Griesbach et al, 2004bGriesbach et al, , 2007. Rats had ad libitum access to food and water and were maintained on a 12-h light/dark cycle.…”
Section: Voluntary Wheel Exercisementioning
confidence: 99%
“…Pumps and drug concentration were chosen to infuse (to rats weighing on average 285 g) 1 mg/kg/day of AMPH or 1.0 μl/h of the vehicle (S) over 7 days. This drug administration method was chosen since our prior studies of RW exposure after TBI have left animals undisturbed for the 1 week exercise period (Vaynman et al, 2003;Griesbach et al, 2004bGriesbach et al, , 2007. The dose was chosen based on the recent report that 1 mg/kg/day of AMPH combined with rehabilitation training facilitates recovery after ischemic brain injury (Adkins and Jones, 2005).…”
Section: Drug Administrationmentioning
confidence: 99%
“…Infusion of TrkB-IgGs was achieved by coupling them to microbeads (Lumaflour Corp., Naples, FL), which we have previously used as a reservoir for the successful delivery of viable inhibitors into the hippocampus (Vaynman et al, 2003). Microbeads were coated via passive absorbency by incubating overnight at 4°C with a 1:5 mix of microbeads to TrkB-IgG 5 μg/μL in PBS with BSA, (Croll et al, 1998) or Cytochrome C (CytC) 100 ng/μL in sterile water (Lom and Cohen-Cory, 1999;Riddle et al, 1997).…”
Section: Bdnf Blockingmentioning
confidence: 99%
“…Our previous efforts have identified the importance of the serine/threonine kinase calcium/ calmodulin protein kinase II (CAMKII) in mediating exercise-induced plasticity in the hippocampus, an area involved in learning and memory formation (Vaynman et al, 2003). Hippocampal CAMKII may likely contribute to perpetuating the effects of exercise on cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristically, exercise has been found to significantly increase BDNF, in the hippocampal area (Neeper et al, 1995;Vaynman et al, 2003), which has been shown to exhibit an abundant expression of the receptor (TrKB receptor) through which BDNF exerts its action (Maisonpierre et al, 1990;Murer et al, 2001). BDNF was initially consigned as a protein regulating the survival, growth, and differentiation of neurons during development (Barde, 1994), but it has become recognized as a critical modulator of synaptic-plasticity in the adult brain (Lo, 1995).…”
Section: Introductionmentioning
confidence: 99%